Learning curves of laparoscopic roux-en-Y gastric bypass and sleeve gastrectomy in bariatric surgery: a systematic review and introduction of a standardization - Wehrtmann, Fabian; Garza, Javier Rodrigo de la; Kowalewski, Karl-Friedrich; Schmidt, Mona Wanda; Müller, Karolina; Probst, Pascal; Diener, Markus K.; Müller, Beat P.; Nickel, Felix (Obesity surgery, 2020)
The most commonly performed bariatric procedures are laparoscopic Roux-en-Y gastric bypass (RYGB) and sleeve gastrectomy (LSG). Impact of learning curves on operative outcome has been well shown, but the necessary learning curves have not been clearly defined. This study provides a systematic review of the literature and proposes a standardization of phases of learning curves for RYGB and LSG.